POLA KOMUNIKASI KELUARGA DALAM NARASI TEKS KISAH AL-QUR’AN; ANALISIS FAMILY COMMUNICATION PATTERNS THEORY - Anggy Rayhana Haswy; Ni'matu Zuhrah; Safrudin (EL-MAQRA', 2025)
This study analyzes family communication patterns in the narrative of Prophet Ibrahim using the Family Communication Patterns Theory (FCPT). Employing qualitative library research and textual analysis of selected Qur’anic verses, the study examines Ibrahim’s interactions with his father Azar, his wife Hajar, and his son Ismail. The findings indicate that: (1) the Qur’an presents prophetic communication as an ethical model for intergenerational transmission of spiritual values, characterized by honesty, gentleness, and respect for human dignity; (2) Ibrahim’s family reflects a Consensual Family type, marked by high conversation and conformity orientations, demonstrated through the harmonious application of six Qur’anic communication principles—qaulan sadīdan, balīghan, layyinan, karīman, ma‘rūfan, and maysūran—balancing open dialogue with strong value commitment; and (3) this model is highly relevant for contemporary Indonesian families, aligning with cultural ideals of familial harmony, respect for parents, and balanced parenting between authoritative and permissive styles. The integration of empirical Western communication theory with normative Islamic perspectives offers an ideal framework for strengthening family relationships, preventing domestic conflict, and developing effective communication models for modern Indonesian society.